Análisis del delito de tráfico de influencias previsto en el código orgánico integral penal - Espinosa Hidalgo, José Miguel (2018)
Abstract:The purpose of the present investigative work is to analyze the offense of influence trafficking foreseen in article 285 of the Ecuadorian integral organic criminal code, from the historical, doctrinal point of view and the conceptions of international organizations which are reflected in the Organic Code criminal integral. Subsequently, the crime in the doctrinal domain and the national regulation in this regard will be analyzed, in consideration of the unlawful conduct, in the same way a doctrinal observation on the protected legal right, its criminalization and the role played by criminal law in public administration, conducting a study of sentences on the crime of influence peddling, ending with the presentation of various conclusions.